An open-source tool for mapping war destruction at scale in Ukraine using Sentinel-1 time series - Olivier Dietrich; Torben Peters; Vivien Sainte Fare Garnot; Valerie Sticher; Thao Ton-That Whelan; Konrad Schindler; Jan Dirk Wegner (Communications Earth & Environment)
Abstract Access to detailed war impact assessments is crucial for humanitarian organizations to assist affected populations effectively. However, maintaining a comprehensive understanding of the situation on the ground is challenging, especially in widespread and prolonged conflicts. Here, we present a scalable method for estimating building damage resulting from armed conflicts. By training a machine learning model on Synthetic Aperture Radar image time series, we generate probabilistic damage estimates at the building level, leveraging existing damage assessments and open building footprints. To allow large-scale inference and ensure accessibility, we tie our method to run on Google Earth Engine. Users can adjust confidence intervals to suit their needs, enabling rapid and flexible assessments of war-related damage across large areas. We provide two publicly accessible dashboards: a Ukraine Damage Explorer to dynamically view our precomputed estimates and a Rapid Damage Mapping Tool to run our method and generate custom maps.